Prenatal Diagnosis of Aorto-Left Ventricular Tunnel With Dysplastic Bicuspid Aortic Valve: From Fetal Cardiac Failure to Favorable Outcome - Truong, Ba Luu; Moreau De Bellaing, Anne; Vialle, Emmanuelle; Haydar, Ayman; Vouhe, Pascal; Jouk, Pierre Simon; Blaysat, Gerard (Frontiers in Pediatrics, 2020)
Abstract Aorto-left ventricular tunnel (ALVT) is a rare congenital heart defect. Surgery has to be performed early to avoid life-threatening complications. Prenatal diagnosis of this defect is challenging. We report a case of ALVT diagnosed in a fetus showing premature severe cardiac failure at 24 GA. The new born was operated at day 3 of life with good results. Two years later, he is still doing well recovering a complete normal cardiac function. ALVT should be suggested in front of any fetal cardiac failure. Thanks to early diagnosis, prompt neonatal management can be organized and allows positive outcome